Strategi Pengembangan Bisnis Halal Dalam Perspektif Manajemen Bisnis Islam - Yuniarti Yuniarti (Annusfy : Journal of Multidisciplinary Research, 2026)
Islamic business management serves as a fundamental framework for establishing business practices based on the values of the Qur'an and Sunnah, enabling organizations to achieve sustainability, competitiveness, and public welfare.  This study employed a qualitative approach using a descriptive method through library research. Data were collected from various academic sources, including books, scholarly journals, and relevant documents discussing Islamic business management and halal business development. The data were analyzed through the processes of data reduction, data presentation, and conclusion drawing. The findings indicate that implementing halal business development strategies from the perspective of Islamic business management enhances business competitiveness, strengthens consumer trust, expands market reach, and promotes sustainable business growth based on Islamic values. The success of these strategies is influenced by the commitment of business actors to uphold the principles of honesty (ṣidq), trustworthiness (amanah), justice, transparency, and professionalism in all business activities. Therefore, integrating modern business strategies with the principles of Islamic business management is essential for supporting the growth of a competitive, sustainable halal industry that contributes to the welfare of society.